ROLE OF CONSUMER PSYCHOLOGICAL STUDIES IN FAST FOOD INDUSTRY - Arshad, Adnan; Khan, Shahzaman; Zafar, Usman; Qadir, Ayesha Abdul (International Journal of Marketing Research Innovation, 2021)
This study examines the behavior of consumer in fast food industry. The customer psychology strongly effected from other customer’s word of mouth, review’s and pricing policy of a company. In this study, we examine the consumer psychology with three factors (referent price, referent deservingness and fair pricing). The three factors become a cause to reduce the anger of consumer and due to this customer satisfy from the operations of fast food industry. We distribute more than 300 questionnaire for analyze our research hypothesis. After analyze we conclude that referent price does not impact on customer anger but it impact on satisfaction of customer. The referent deservingness and price fairness has significant impact on anger of customer and satisfaction of customer. This study provides useful information to fast food sector regarding customer psychology.